Development of citizenship indicators for students in three southern provinces - dearamae, a-i-dah; Rorbkorb, Narongsak; Tansakul, Jirawat; Rascha, Teerayout (Al-HIKMAH Journal, 2024)
The objective of this research is to develop and validate the quality indicators of citizenship among students in the border areas of three southern provinces. The research consists of two steps: Step 1 involves developing indicators synthesized from various relevant research works, while Step 2 focuses on validating the suitability and feasibility of these citizenship indicators among students in the border areas. The evaluation involves: Expert assessment by 5 specialists. Assessment by teachers of social studies, religion, and culture or teachers responsible for additional social studies subjects for Grade 6 students in the border areas of the three southern provinces, totaling 30 students. The assessment tool used is a suitability and feasibility assessment of the citizenship indicators for students in the southern border provinces. Data analysis includes statistical analysis, mean values, and standard deviations. The assessment tool used is a suitability and feasibility assessment of the citizenship indicators for students in the southern border provinces. Data analysis includes statistical analysis, mean values, and standard deviations.The research findings revealed that the indicators of citizenship quality among students in the southern border provinces comprised 4 components and 20 indicators. The indicators were found to be appropriate and feasible for use based on predetermined criteria, with an overall mean score ( = 4.59 , S.D = 0.52 ). Assessment of the suitability of the indicators yielded mean scores ranging from 4.20 to 4.80, while feasibility for use had mean scores ranging from 4.20 to 4.80.